Factors affecting the effectiveness of personal protective equipment (PPE) / Nur Farhani Nor ‘Azizan - Nor ‘Azizan, Nur Farhani (2015)
The purpose of this study was to determine factors affecting the effectiveness of personal protective equipment (PPE). The variables consist of employer responsibilities, work environment and worker attitudes that are stated as independent variables for this study. The respondents were 327 employees from six (6) different divisions and department in Northport (Malaysia) Bhd which are Conventional Cargo and Logistic Services Division, Marine Division, Equipment and Maintenance Division, Container Division, Facilities Division and HSE, Fire and Rescue Department. The findings showed that all three independent variables have a positive and strong relationship with dependent variable, the effectiveness of personal protective equipment. This implies that, employer at Northport (Malaysia) Bhd comply a very good responsibilities in ensuring worker safety when working at site locations. They often request OSHA committee member to do inspection at work environment as to improve safety security of workplace. In the meanwhile, worker attitudes from times to times gaining improvement in term of self-discipline when undergoing hazardous working conditions.